2012
DOI: 10.1002/sres.2137
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Strategic and Tactical Flexibility in Managing Input Variability on Farms

Abstract: Accepting that increased climate variability will require that farmers make significant changes to their farm systems, we can see that maintaining flexibility is an important coping strategy. Using general systems theory, we offer a conceptual model for describing the tactical and strategic flexibility of farm systems to reveal the sensitivity of farm systems to variable critical inputs. The model is used to classify farm systems as rigid, robust, or elastic on the basis of two factors, the capacity of the far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The ability to include interannual variability for profit maximization and risk minimization is a permanent challenge for pastoral farmers (Vogeler et al, 2016) that require maintaining high flexibility of the systems (Cowan, Kaine, & Wright, 2013). Previous studies in the same region have shown the benefits of technological systems on average rainfall conditions (Fernández Rosso et al, 2018;Lauric et al, 2016).…”
Section: A Potential Path For Farm Innovationmentioning
confidence: 99%
“…The ability to include interannual variability for profit maximization and risk minimization is a permanent challenge for pastoral farmers (Vogeler et al, 2016) that require maintaining high flexibility of the systems (Cowan, Kaine, & Wright, 2013). Previous studies in the same region have shown the benefits of technological systems on average rainfall conditions (Fernández Rosso et al, 2018;Lauric et al, 2016).…”
Section: A Potential Path For Farm Innovationmentioning
confidence: 99%
“…The 'fuzziness' of resilience can encompass a number of other related topics including adaptability, flexibility, coping capacity, sustainability, and transformation (Rodriguez and Sadras 2011;Berman et al 2012;Cowan et al 2013;Marshall et al 2013a). Furthermore, some scholars may be disinclined to use the term (Olsson et al 2015), for example due to conceptual, theoretical, or ontological differences between disciplines (McEvoy et al 2013;Nelson 2011).…”
Section: Conclusion and Suggestions For Future Researchmentioning
confidence: 99%
“…Understanding how farmers manage variability in farm inputs has been the focus of an area of applied research, grounded in general systems theory [40] and cybernetics [37], which is described here as production control theory [41,42] (described in Cowan [8] as farm control theory). While the focus here is on farms, production control theory has relevance to system regulation processes in business production systems more generally.…”
Section: Farm-environment Interaction: Production Controlmentioning
confidence: 99%
“…For example, it has been applied to farming experiences in the Sunraysia region of northern Victoria to analyse the impacts of climatic variability on grape producers [27]. Here, elements from production control theory from Cowan, Kaine and Wright [42] and Kaine and Cowan [41] are summarized with a focus on concepts that are central to considering how managing variability in inputs constrains decision-making.…”
Section: Farm-environment Interaction: Production Controlmentioning
confidence: 99%
See 1 more Smart Citation